Zinc Biofortification of Rice Using Fish Protein Hydrolysates Mixed With Zinc Sulfate. - Sjaifullah, Achmad (UNEJ e-Proceeding, 2014)
Zinc deficiency is one of the serious health problems experienced by half of the world population who consumes rice as a staple food. Zn biofortification of rice is aimed to increase the concentration of Zn, and its bioavailability in rice is one of a growing research. Some of the compounds used in Zn biofortification include Zn sulfate, Zn EDTA, Zn nitrate, Zn chloride, Zn organic and Zn amino acids (i.e., a combination of ZnSO4 and amino acids). Among those various compounds of zincs, Zn biofortification of rice by foliar application of solution ZnSO4 mixed with amino acid is the best in improving the concentration of Zn in polished rice and also its bio-availability. This article discusses the effect of the use of fish protein hydrolysate solution containing amino acids and peptides added with ZnSO4 for zinc biofortification of rice. Fish hydrolysate solution mixed with ZnSO4 were applied by foliar spraying on rice in three applications at intervals of 8 days, starting 73 days after planting, when the rice begins to flower. Spraying was performed in the morning, between 08:00 - 09:30 oâclock on the samples and the control plots. The results showed that the rice crop sprayed with fish hydrolysate mixed with ZnSO4 has increased the rice production by 7 % in weight and the polished rice which was sprayed with fish hydrolysate mixed with ZnSO4 contains 40 % higher of Zn (17.1 ppm) than in controls (12.0 ppm). Keywords: zinc biofortification, fish protein hydrolysate, zinc sulfates.